LITERATURE REVIEW : EFEKTIVITAS PROGRAM ANTI-BULLYING BERBASIS KETAHANAN DALAM MENCEGAH PERILAKU BULLYING - Resti Utami (Jurnal Kesehatan dr. Soebandi, 2020)
Bullying is characterized by an imbalance of power in relationships, which can lead to negative social consequences. These new findings indicate that interventions must focus on supporting victims of bullying to help build resilience and bullying actors to be able to control emotions through a resilience approach. Nurses can develop effective strategies for dealing with this form of bullying and its consequences for victims. This review aims to gather evidence in the form of Literature Review about the effectiveness of a resilience-based anti-bullying program to prevent bullying. The method used in this Literature review begins with the selection of topics, then keywords are determined for journal searched. Management of bullying can not only reduced the symptoms of mental health of children but also prevent mental difficults and deliver children to be able to growth and develop optimal throughout the child's life cycle. Children with higher levels of endurance tend not to engaged in aggressive behavior or become victims of bullying.